Participación del factor de crecimiento fibroblástico 2 (FGF2) y sus receptores (FGFRs) en la regulación de la fisiología espermática - Saucedo, Lucía (2017)
The signaling mediated by the fibroblast growth factor 2 (FGF2) and its receptors (FGFRs) has been widely described in somatic cells, but there is scarce evidence of its function in the gametes. The main objective of this work was to characterize the expression of FGF2 and FGFRs in mammalian reproductive tissues and gametes, and to establish their role in the regulation of sperm physiology. The human and murine models were used.\nThe results in the human model showed: 1) the presence and localization of FGF2 and FGFRs in sperm cells and testis, 2) the beneficial effect of recombinant FGF2 (FGF2r) on sperm motility and on sperm recovery in a selection technique, 3) the relationship between FGF2 sperm levels and other seminal parameters. In the murine model, the results showed: 1) the presence and localization of FGF2 and FGFRs in gametes and reproductive tissues, 2) the effect of the addition of FGF2r upon several sperm parameters, 7) defects in sperm physiology and in the spermatogenesis process in FGF2 knock-out mice.\nIn conjunction, the results provide evidence of the presence and function of FGF2/ FGFRs system in sperm cells and reproductive tissues, and might eventually contribute to propose new tools for the diagnosis and treatment of male infertility.